Influence of Different Filling, Cooling, and Storage Conditions on the Growth of Alicyclobacillus acidoterrestris CRA7152 in Orange Juice - Spinelli, Ana Cláudia N. F. (American Society for Microbiology (ASM), 2009)
The prevention of spoilage by Alicyclobacillus acidoterrestris is a current challenge for fruit juice and beverage industries worldwide due to the bacterium's acidothermophilic growth capability, heat resistance, and spoilage potential. This study examined the effect of storage temperature on A. acidoterrestris growth in hot-filled orange juice. The evolution of the A. acidoterrestris population was monitored under six different storage conditions after pasteurization (at 92°C for 10 s), maintenance at 85°C for 150 s, and cooling with water spray to 35°C in about 30 min and using two inoculum levels: <10(1) and 10(1) spores/ml. Final cooling and storage conditions were as follows: treatment 1, 30°C for the bottle cold point and storage at 35°C; treatment 2, 30°C for 48 h and storage at 35°C; treatment 3, 25°C for the bottle cold point and storage at 35°C; treatment 4, 25°C for 48 h and storage at 35°C; treatment 5, storage at 20°C (control); and treatment 6, filling and storage at 25°C. It was found that only in treatment 5 did the population remain inhibited during the 6 months of orange juice shelf life. By examining treatments 1 to 4, it was observed that A. acidoterrestris predicted growth parameters were significantly influenced (P < 0.05) either by inoculum level or cooling and storage conditions. The time required to reach a 10(4) CFU/ml population of A. acidoterrestris was considered to be an adequate parameter to indicate orange juice spoilage by A. acidoterrestris. Therefore, hot-filled orange juice should be stored at or below 20°C to avoid spoilage by this microorganism. This procedure can be considered a safe and inexpensive alternative to other treatments proposed earlier.